Violence and violations of the feminine body in Conceição Evaristo’s novel Sabela - Alves-Garbim, Juliana Franco [UNESP] (Associacao Internacional de Lusitanistas, 2024)
The present work focuses on the literary construction of Conceição Evaristo through the look of Afro-feminine culture, as well as the denunciative character about the corporal and psycho-emotional violence resulting from the aggressions imposed on black women by the sexism of patriarchy. The intention is to subvert the reader’s gaze to see the history of black women in Brazil from a matrifocal perspective, as the novel Sabela draws attention, present in Histórias de leves enganos e parecenças (Evaristo, 2017). To this end, we aim to reflect on the importance of the role of women in Brazilian society and the relationship with the black body, which stand out in the tales of the Afrocentric theme. In the analysis, the epistemological bases have theorists such as Stuart Hall (2003), Lélia González (2020), among other researchers of the Afro-Brazilian and culturalist theme. The methodological procedures involved consist of a qualitative analysis of the novel circumscribed to the axiological universe of Conceição Evaristo, with ways to identify traces that highlight symbolic violence, material and bodily to this day sustained by the white and hegemonic culture on the black woman’s body. Here, we construct the hypothesis that the discussion on the theme promotes the fight against racial sexism while at the same time increasing the visibility and promotion of gender and cultural equality. In this context, the contributions of the research point to the positive aspect of (re)construction and strengthening of the Afro-female culture regarding aesthetic-literary and social diversity.
Violências e violações do corpo feminino na novela “Sabela”, de Conceição Evaristo
Keywords: Afro-Brazilian literature; Conceição Evaristo; feminine; violence